Long-term quercetin supplementation reduces lipid peroxidation but does not improve performance in endurance runners - Scholten SD; Sergeev IN (Dove Medical Press, 2013)
Shane D Scholten,1 Igor N Sergeev21Department of Natural Sciences, University of Sioux Falls, Sioux Falls, SD, USA; 2Department of Health and Nutritional Sciences, South Dakota State University, Brookings, SD, USAPurpose: To evaluate the effects of chronic quercetin supplementation on endurance performance and antioxidant status in long distance runners. We hypothesized that an improved antioxidant status can be associated with enhanced performance.Methods: During 6 weeks of supplementation utilizing a double blind, randomized design, young male subjects received quercetin (1000 mg/day) or placebo while maintaining their current training schedules.Results: Following the end of the supplementation period, there was a significant time × supplement interaction for serum malondialdehyde (MDA), an indicator of lipid peroxidation. There were no significant pre- to post-supplement changes in parameter values employed for measuring total antioxidant capacity, superoxide dismutase activity, and protein oxidation (protein carbonyl) in serum. There were also no significant pre- to post-supplement differences in VO2peak, running economy, heart rate, and rating of perceived exertion (RPE) during the 10 km time trial.Conclusion: The findings obtained indicate that there is a relationship between quercetin supplementation and the statistically significant decreasing trend in MDA levels following 6 weeks of supplementation and training. This evidence suggests that quercetin can reduce oxidative stress (lipid peroxidation). However, performance improvements were not significant (as measured by VO2peak, running economy, heart rate, and RPE).Keywords: quercetin, antioxidant capacity, oxygen consumption, running economy, exercise performance